Depression among Urban Adolescent Students of Some Selected Schools (Faridpur Medical College Journal, 2015)
To determine the factors related with depression among adolescent students, 165 male adolescent students aged 15 to 19 years from 2 urban schools and colleges were interviewed with semi-structured questionnaire during January to June 2012.The socio demographic details, smoking and depression histories were recorded. The Center for Epidemiologic Studies Depression Scale (CES-D) was used to measure the presence of depression. Smoking behavior was measured by a number of questions. Almost 49% respondents were depressed and 66% were smokers. Most of the respondents started smoking around the age of 14.3 years (54.1%) by the influence of their friends. Among the smokers 82.7% were depressed while 17.3% were depressed among nonsmokers (?2=19.69, p=